MARKET REACTION ANALYSIS BEFORE AND AFTER THE ANNOUNCEMENT OF THE DIVIDEND (EMPIRE STUDY ON GO PUBLIC COMPANIES) - Affandi, Muhammad Rispan; Amalia, Tengku Putri (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
The purpose of this study is to prove whether there are differences in the volume of stock trading in the period and whether there are differences in abnormal returns before and after the announcement of cash dividends in Property and Real Estate companies on the Indonesia Stock Exchange. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange as many as 360 companies with years of observation 201 1 to 201 6 . The sample was selected using purposive sampling method . The data was processed using the panel data regression statistical test method. The results of this study prove that the announcement of cash dividends does not cause stock trading volume to change after the announcement of dividends and there is no difference in the average abnormal return in the period before and after the announcement of cash dividends in Property and Real Estate companies on the Indonesia Stock Exchange .